A Molecular Approach to Self‐Supported Cobalt‐Substituted ZnO Materials as Remarkably Stable Electrocatalysts for Water Oxidation1. Issue 20 (28th April 2014) - Pfrommer, Johannes; Lublow, Michael; Azarpira, Anahita; Göbel, Caren; Lücke, Marcel; Steigert, Alexander; Pogrzeba, Martin; Menezes, Prashanth W.; Fischer, Anna; Schedel‐Niedrig, Thomas; Driess, Matthias
Abstract In regard to earth‐abundant cobalt water oxidation catalysts, very recent findings show the reorganization of the materials to amorphous active phases under catalytic conditions. To further understand this concept, a unique cobalt‐substituted crystalline zinc oxide (Co:ZnO) precatalyst has been synthesized by low‐temperature solvolysis of molecular heterobimetallic Co4−xZnxO4 (x=1–3) precursors in benzylamine. Its electrophoretic deposition onto fluorinated tin oxide electrodes leads after oxidative conditioning to an amorphous self‐supported water‐oxidation electrocatalyst, which was observed by HR‐TEM on FIB lamellas of the EPD layers. The Co‐rich hydroxide‐oxidic electrocatalyst performs at very low overpotentials (512 mV at pH 7; 330 mV at pH 12), while chronoamperometry shows a stable catalytic current over several hours.